NCI-CONNECT: Comprehensive Oncology Network Evaluating Rare CNS Tumors—Histone Mutated Midline Glioma Workshop Proceedings. Issue 1 (16th January 2020) - Theeler, Brett J; Dalal, Yamini; Monje, Michelle; Shilatifard, Ali; Suvà, Mario L; Aboud, Orwa; Camphausen, Kevin; Cordova, Christine; Finch, Elizabeth; Heiss, John D; Packer, Roger J; Romo, Carlos G; et al.
Abstract: Histone mutations occur in approximately 4% of different cancer types. In 2012, mutations were found in the gene encoding histone variant H3.3 ( H3F3A gene) in pediatric diffuse intrinsic pontine gliomas and pediatric hemispheric gliomas. Tumors with mutations in the H3F3A gene are generally characterized as histone mutated gliomas (HMGs) or diffuse midline gliomas. HMGs are a rare subtype of glial tumor that is malignant and fast growing, carrying a poor prognosis. In 2017, the Beau Biden Cancer Moonshot Program appropriated 1.7 billion toward cancer care in 10 select areas. The National Cancer Institute (NCI) was granted support to focus specifically on rare central nervous system (CNS) tumors through NCI-CONNECT. Its mission is to address the challenges and unmet needs in CNS cancer research and treatment by connecting patients, providers, researchers, and advocacy organizations to work in partnership. On September 27, 2018, NCI-CONNECT convened a workshop on histone mutated midline glioma, one of the 12 CNS cancers included in its initial portfolio. Three leaders in the field provided an overview of advances in histone mutated midline glioma research. These experts shared observations and experiences related to common scientific and clinical challenges in studying these tumors. Although the clinical focus of this workshop was on adult patients, one important objective was to start a collaborative dialogue between pediatric and adult clinicians and researchers. Meeting participants identified needs for diagnostic and treatment standards, disease biology and biological targets for this cancer, disease-specific trial designs, and developed a list of action items and future direction.